Iron-Catalyzed Oxidative Decarboxylation of Oxamic Acids: A Safe and Efficient Photochemical Route to Urethanes - Kurtay, Gülbin; Lusseau, Jonathan; Robert, Frédéric; Landais, Yannick (Synlett, 2023)
This study presents a facile method for synthesizing urethanes through the photocatalyzed oxidative decarboxylation of oxamic acids. The process involves the formation of an isocyanate in situ from an oxamic acid under blue-light irradiation (427 nm) in the presence of ferrocene as a photocatalyst, 2-picolinic acid as a ligand, and potassium bromate as an oxidant. The one-pot procedure effectively avoids the need for separation, purification, and storage of carcinogenic isocyanates, making it a safer and more practical method for obtaining target urethanes from easily accessible starting materials.
Keywords: urethanes; oxamic acids; iron catalysis; ferrocene; photocatalysis; decarboxylation